HISTOMORPHOMETRI OF WHITE BLOOD CELLS OF BALI DUCKS USING HISTOCHEMICAL METHODS - I Gusti Ngurah Jagad Anom Ksatriya; Ni Ketut Suwiti; Anak Agung Sagung Kendran; Ni Luh Eka Setiasih; I Ketut Suatha; Ni Nyoman Werdi Susari (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Bali ducks are one of the local poultry breeds whose meat and eggs are usually used. Bali ducks can experience immune disorders, especially their susceptibility to disease. White blood cells can be used as an indicator of the infection in the body, so white blood cell examination is necessary to evaluate livestock health. This study aims to determine the histomorphometric structure and differences in white blood cells in male and female Bali ducks. This research used blood samples from 8 male Balinese ducks and 8 female Balinese ducks aged two to three months from farms in Mengwi District, Badung Regency. Staining of blood smear was carried out using eosin and methylene blue staining (MDT IndoReagen®). Examination and measurement of blood cell preparations were carried out using an Olympus CX33 microscope and EPView application. Data analysis was carried out using independent samples T-test with the help of SPSS software. The results of histomorphometric examination showed that the heterophyll diameter of male Bali ducks was 5.38±0.62 µm, and the female Bali ducks was 5.23±0.60 µm. The eosinophil diameter of male Bali ducks was 5.49±0.62 µm, and the female Bali ducks was 4.99±0.54 µm. The basophil diameter of male Bali duck was 3.82±0.35 µm, and the female Bali duck was 4.33±0.52 µm. The monocyte diameter of male Bali duck was 5.13±0.72 µm, and the female Bali duck was 4.99±0.37 µm. The lymphocytes diameter of male Bali duck was 4.18±0.74 µm, and the female Bali duck was 4.52±0.58 µm. Based on the research results, it can be concluded that there is no histomorphometric difference between the white blood cells of male and female Bali ducks (P>0.05). Further research is needed regarding the histomorphometric comparison of white blood cells in Bali ducks at different ages to obtain more complete data.